Oxidative stress response as biomarker of exposure of a freshwater invertebrate model organism (Unio mancus Lamarck, 1819) to antifouling copper pyrithione - Paçal, Elif; Gümüş, Burçin Aşkım; Günal, A. Çağlan; Erkmen, Belda; Arslan, Pınar; Yıldırım, Zuhal; Erkoç, Figen (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2022)
Sublethal effects of copper pyrithione (CuPT) on an invertebrate model organism, freshwater mussel (Unio mancus), were assessed using oxidative stress parameters and histopathology. The environmentally relevant concentration of 5 μg/l copper pyrithione was applied as a 96 h semi-static exposure. MDA levels in digestive gland (DG) significantly increased, compared to a control group (p < 0.001). Gill MDA levels also increased, but not significantly (p > 0.05). GSH level in DG increased significantly (p < 0.05), and gill tissue levels also increased but not significantly (p > 0.05). Levels of SOD, GPx activities, and AOPP levels did not change significantly (p > 0.05). The most prominent histopathological alterations in the gills were haemocyte infiltration, lipofuscin aggregates and lamellar deformations with tubule degeneration and accumulated lipofuscin aggregates in DG tubules. CuPT impacts antioxidant defense systems even during sublethal exposure of Unio mancus as the freshwater model organism.